Aplicación de instrumentos de gestión como contribución a la mejora productiva del sector minorista de lácteos en el cantón Bolívar. - Bombón Cunalata, Yeremy Aldair (2018)
The main objective of the research was the application of management tools to the dairy retail sector of Bolívar canton, allowing a contribution to the productive improvement within the sector. Outlining, a bibliographic review was applied to identify the techniques or indicators to measure the functioning of the critical success factors within the scope of the productive management of the dairy retail sector, using media such as scientific articles, books, and reliable electronic documents between others, then proceeded to make the selection of the relevant techniques of each of the decision areas for improvement in productive management, which reflects that for the PROCESS factor was selected the following techniques (process map, process cards, flowchart), HUMAN RESOURCES (analysis and design of posts), CAPACITY (proportional method), INVENTORY (MRP- Material Requirements Program) and for QUALITY (Risk analysis systems and critical control points). Concluding with the respective application of the selected techniques or indicators in the respective decision areas, it is evident that these critical factors of success contribute to the productive management of the dairy sector of Bolívar canton, which farmers who work in this sector do so in a conventional manner without theoretical or scientific foundations, that allow them to determine their net profits and the recovery of the investment executed in said work. Finally, the application of the management instruments was presented to the people who incur in this sector for its progress.